The international currency system: New challenges and opportunities in the context of global changes - Sukhyi, Dmytro; Kopylova, Olha; Motorniuk, Uliana; Larionova, Katerina; Klimova, Inna (Edelweiss Applied Science and Technology, 2024)
The purpose of the article is to analyze the reform of the world monetary system and find mechanisms for its independent regulation, the use of competitive currencies for international transactions, especially decentralized ones such as cryptocurrency, or the creation of a super-sovereign global currency, which will be independent of the politics of certain countries. The systematization, assessment, and analysis of the main elements of the international monetary system were carried out by reviewing the literature of recent years and analyzing the open databases of the International Monetary Fund website to observe the theoretical and methodological foundations of the international monetary system, in order to determine its advantages and disadvantages, as well as to find promising directions for its reform during global changes. The unfairness and instability of the world currency during the economic crisis have caused significant losses for countries that do not own world currencies. This fact requires new approaches to regulating and reforming the currency system. One of the solutions could be the creation of an independent international currency that would preserve the monopolarity of the world currency and exclude the influence of the issuing countries on the value of the world currency. The analysis of world currency reserves revealed the prevailing share of the dollar at over 60% and the euro at about 20%. Among the possibilities, it is worth considering blockchain cryptocurrency technology, which could become the basis for the creation of an independent world currency and the development of an electronic global currency that would meet the demands of society. The international monetary system needs to be reformed; one of the promising directions should be the creation of an independent global currency with regulation in accordance with the interests of the world, ignoring the interests of the issuing countries.